Мәңгілік қайта оралу шежіресі туралы: мифтен физикаға және одан әрі - Safronov, D.G. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2021)
Abstract: Guided to the notion of the eternal return by the philosophical intuitions of the Greek antiquity, Nietzsche turned to the physical sciences of his day in order to further his inquiry. This extensive intellectual engagement represented a genuine attempt to investigate the possible continuity of meaning between the mythical tradition, on the one hand, and the rational-empirical (i.e. scientific), on the other. In particular, Nietzsche was captivated by the manner in which the relationship between myth and science played out in the connection between the eternal return and entropy. Blocking the possibility of testing his hypothesis lay the debris of metaphysical imports into the discourse of secular modern science. Nietzsche’s task – akin to Hercules’ fifth labour[1] – transformed into the project of disentangling scientific learning from the implicit metaphysical precepts. In the course of this ambitious undertaking – from the untangling of physics and metaphysics – Nietzsche discerned a possibility for synthesising the scientific explanation for his ‘fundamental conception’ (EH: Z, §1) with the mythical wisdom of the ages. His inferences proved nothing short of explosive. The doctrine of the eternal return of the same, instead of the docile cosmic torpor, urged the radical revaluation of all values. The measure of the eternal return’s power was to dissolve its impersonation – the Übermensch – into a form of well-being. Nietzsche was convinced that his ‘mightiest idea’ (NF-1881:11[148]) illuminated the path we must follow lest we wish to incur the full force of the ‘frightening wisdom of Silenus’ (BT: §4).[2] Key words: Entropy, physics, religion, eternal return, thermodynamics, myth, knowledge, science, genealogy, capitalism